2017
DOI: 10.1021/jacs.7b01431
|View full text |Cite
|
Sign up to set email alerts
|

Genetically Encoded Photoaffinity Histone Marks

Abstract: Posttranslational modifications (PTMs) of lysine are crucial histone marks that regulate diverse biological processes. The functional roles and regulation mechanism of many newly identified lysine PTMs, however, remain yet to be understood. Here we report a photoaffinity crotonyl lysine (Kcr) analogue that can be genetically and site-specifically incorporated into histone proteins. This, in conjunction with the genetically encoded photo-lysine as a "control probe", enables the capture and identification of enz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
44
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(44 citation statements)
references
References 41 publications
0
44
0
Order By: Relevance
“…[30] Furthermore,anUAA functionalized with both adiazirine moiety attached to the Cg-position of lysine and carrying ac rotonyl group at the Ne-position was synthesized and successfully incorporated into proteins using an engineered PylRS mutant. To investigate lysine PTM-mediated protein-protein interactions,Xie et al developed photocrosslinker UAAs that contain ad iazirine moiety introduced into the backbone of the lysine side chain, rather than attached to the Ne-amino group of lysine.T his frees the Ne-amino group (after enzymatic in vivo reduction of a p-nitrobenzyloxycarbonyl protecting group) for recognition and subsequent trapping of (histone) modifying and interacting proteins (8,F igure 5).…”
Section: Elucidating the Protein Interactome In Chromatin Biologymentioning
confidence: 99%
See 1 more Smart Citation
“…[30] Furthermore,anUAA functionalized with both adiazirine moiety attached to the Cg-position of lysine and carrying ac rotonyl group at the Ne-position was synthesized and successfully incorporated into proteins using an engineered PylRS mutant. To investigate lysine PTM-mediated protein-protein interactions,Xie et al developed photocrosslinker UAAs that contain ad iazirine moiety introduced into the backbone of the lysine side chain, rather than attached to the Ne-amino group of lysine.T his frees the Ne-amino group (after enzymatic in vivo reduction of a p-nitrobenzyloxycarbonyl protecting group) for recognition and subsequent trapping of (histone) modifying and interacting proteins (8,F igure 5).…”
Section: Elucidating the Protein Interactome In Chromatin Biologymentioning
confidence: 99%
“…To investigate lysine PTM-mediated protein-protein interactions,Xie et al developed photocrosslinker UAAs that contain ad iazirine moiety introduced into the backbone of the lysine side chain, rather than attached to the Ne-amino group of lysine.T his frees the Ne-amino group (after enzymatic in vivo reduction of a p-nitrobenzyloxycarbonyl protecting group) for recognition and subsequent trapping of (histone) modifying and interacting proteins (8,F igure 5). [30] Furthermore,anUAA functionalized with both adiazirine moiety attached to the Cg-position of lysine and carrying ac rotonyl group at the Ne-position was synthesized and successfully incorporated into proteins using an engineered PylRS mutant. (9,F igure 5).…”
Section: Elucidating the Protein Interactome In Chromatin Biologymentioning
confidence: 99%
“…PAL provides a snapshot of the probe's interactions at a given time‐point, and can be highly valuable in target identification, target validation and selectivity profiling, which will be discussed in this section. Additionally, this approach has found utility in mapping macromolecular interactions using genetically encoded amino acids bearing photoreactive groups, however this is outside the scope of this review.…”
Section: Capturing Reversible Interactionsmentioning
confidence: 99%
“…[36] The authors demonstrated that metabolic labeled bifunctional sugars can efficiently crosslink CD22 protein in an oligomeric form under UV light and that the crosslinked product can be analyzed by streptavidin after a click reaction with a biotin handle. [43] HdeA 5 amber codon suppression tmdPhe [27] GRB1-SRC 5 amber codon suppression TmdZLys [44] EGFR 15 amber codon suppression DiZSeK [45] GFP, HdeA 10 amber codon suppression pAzpa, pBzpa [46] HSP90-Aha1 120 amber codon suppression DiZHSeC [ 30a] HdeA-DegP 10 amber codon suppression DiZASeC [ 30b] Deg-p 10 amber codon suppression PNBK*, K*Cr [47] enzymatic machinery of histone PTM 15 amber codon suppression Abk [26] H3, H4 histones 10 amber codon suppression photomethionine, photoleucine [23] PGRMC1 3 surrogate photolysine [24] readers and erasers of lysine PTM 20 surrogate 4 [34] GM1 n.a. glycosylation GlcNDAz derivatives [48] AGX1 n.a.…”
Section: Enzymatic Incorporation Of Photocrosslinkers On a Target Promentioning
confidence: 99%